Auguste Comte and Consensus Formation in American Religious Thought—Part 2: Twilight of New England Comtism - Kenneth S. Sacks (Religions, 2017)
Auguste Comte was the most influential sociologist and philosopher of science in the Nineteenth Century. Part 1 summarized his works and analyzed reactions to them by Transcendentalists and Unitarians from 1837 until just after the Civil War. Part 2 examines in detail the post-war Transcendentalist and liberal Unitarian institutions of the Free Religious Association and the Radical Club and their different approaches to spiritual faith based on intuitionalism and reliance on scientific proof. In the background to their disputes is the positivism of Auguste Comte, who served as an easy source of common criticism. But at the same time as they wrote against positivism, both intuitionalists and those who relied on science were significantly influenced by Comte. Once again, as in part 1, a community of discourse was formed through the need to create social bonds at the expense of careful evaluation of the philosophy they criticized.